2022
DOI: 10.1021/acsearthspacechem.2c00122
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Modeling of the Oxidation Mechanism of Co(II) by Birnessite

Abstract: Phyllomanganates of the birnessite family are the most abundant manganese oxides on Earth and the strongest inorganic oxidants in the environment. Birnessite controls the oxidative scavenging of cobalt in soils, lake and marine sediments, and ferromanganese crusts and nodules, leading to enrichments of the order of one billion times the concentration in solution. However, a detailed mechanistic understanding of the enrichment processes is lacking. Here, we perform density functional theory (DFT) calculations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 150 publications
0
12
0
Order By: Relevance
“…The oxidation of various elements by sorption on birnessite was shown earlier for Co­(II), I 2 and I – , , Cr­(III), As­(III), and TcO 2 . Actually, birnessite demonstrates the highest oxidative ability compared with other common minerals, including manganese-containing minerals .…”
Section: Resultsmentioning
confidence: 70%
“…The oxidation of various elements by sorption on birnessite was shown earlier for Co­(II), I 2 and I – , , Cr­(III), As­(III), and TcO 2 . Actually, birnessite demonstrates the highest oxidative ability compared with other common minerals, including manganese-containing minerals .…”
Section: Resultsmentioning
confidence: 70%
“…Spin-unrestricted DFT calculations were performed on cluster models with ORCA 5.0.3 and a computational methodology similar to that used previously to study the complexation energetics of Co­(II)/Co­(III), Ni­(II), Cu­(II), Zn­(II), and Pb­(II) on birnessite. , In ref , we investigated the effect of the size of the birnessite model on DFT results. Using protons to yield (nearly) charge-neutral, symmetric systems, we found that a cluster model with 18 Mn­(IV) octahedra provides robust results.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The accuracy of prediction of Δ G obtained with the afore-described computational methodology has been benchmarked previously , with the first hydrolysis constants of the hexahydrated Mn 2+ , Co 2+ , Ni 2+ , and Zn 2+ ions . Δ G values for these ions are calculated reliably within chemical accuracy (1–2 kcal/mol).…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations